Mechanical and Chemical Signaling in Angiogenesis - Reinhart-King, Cynthia A. (Studies in Mechanobiology, Tissue Engineering and Biomaterials, 2013)
This volume of Studies in Mechanobiology, Tissue Engineering and Biomaterials describes the most recent advances in angiogenesis research at all biological length scales: molecular, cellular and tissue, in both in vivo and in vitro settings.  Angiogenesis experts from diverse fields including engineering, cell and developmental biology, and chemistry have contributed chapters which focus on the mechanical and chemical signals which affect and promote blood vessel growth. Specific emphasis is given to novel methodologies and biomaterials that have been developed and applied to angiogenesis research. .